Progressive Jews in Argentina and the Arab-Israeli Conflict : Stances on the Six-Day War (1967) - Kahan, Emmanuel Nicolás (2019)
Desde la resolución de 1947 de las Naciones Unidas sobre la partición de Palestina y, posteriormente, la Declaración de Independencia de Israel en 1948, el problema israelípalestino ha desempeñado un papel importante en el espacio público argentino que no ha encontrado una respuesta concomitante en el mundo académico. La postura con respecto a la Guerra de los Seis Días de 1967 tomada por una institución que se promueve a sí misma como representante de los judíos progresistas argentinos, el Idisher Cultur Farband (Federación Argentina de Instituciones Culturales Judías-ICUF), socavó ciertos significados, vínculos de solidaridad y modos de representación de una diversidad de actores con respecto a la existencia y legitimidad del Estado de Israel.
Since the 1947 United Nations resolution on the partition of Palestine and, subsequently, the Israeli Declaration of Independence in 1948, the Israeli-Palestinian issue has played a powerful role in Argentine public space that has not found a concomitant response in academia. The stance with regard to the 1967 Six-Day War taken by an institution that promotes itself as representative of progressive Argentine Jews, the Idisher Cultur Farband (Argentine Federation of Jewish Cultural Institutions-ICUF), undermined certain meanings, ties of solidarity, and modes of representation held by a diversity of actors regarding the existence and legitimacy of the State of Israel.
Keywords: Israel; Palestina; Comunistas; Judíos; Argentina; Israel; Palestine; Communists; Jews; Argentina; Judíos; Guerra; Israel; Palestina